Sports Development (Systematic Literature Review) - Muhammad Rizky Putramadiansyah; Salahudin Salahudin (JUARA : Jurnal Olahraga, 2021)
This scientific paper aims to examine the scientific articles of international repute that discuss Sports Development. The research method that is used in this research is the bibliometric analysis method. The process of bibliometric analysis includes; data extraction, processing, networking, interpretation, and visualization. The findings in this study indicate that there are 406 interrelated articles. The articles are divided into 3 clusters. Cluster 1 relates to the parties involved in the sports development planning process and the prioritized criteria in the discourse on sports development. Then cluster 2 emphasizes the data that used as a benchmark for sports development. Last, three is about the goals to be achieved in sports development.